Temporal–spatial dynamics of typical ecosystem services in the Chaobai River basin in the Beijing-Tianjin-Hebei urban megaregion - Zhang, Jiping; Liu, Chunlan; Wang, Hui; Liu, Xiaona; Qiao, Qing (Frontiers in Ecology and Evolution, 2023)
Human demand for ecosystem services dominates ecosystem changes, and impact the temporal-spatial patterns of ecosystem services and their trade-offs. In the process of urbanization, the supply service, regulation service and cultural service of ecosystem are difficult to improve in synergies in the city and its surrounding areas, which is tough for urban construction and development. This study took the Chaobai River basin located in the Beijing-Tianjin-Hebei urban megaregion in northern China as the research area. The temporal and spatial changes of three typical ecosystem services, including food production, water conservation and recreation, in the study area from 2000 to 2015 were evaluated and analyzed through modeling. The ecosystem service hotspots, service-gain area and service-loss area were identified based on spatial analysis. The dynamic change mechanism of ecosystem services were explored from the perspective of land use change and hotspots analysis. The results showed that: (1) recreation and food production services showed an increasing trend, while water conservation showed a fluctuating increasing trend. (2) The service-gain area was significantly larger than service-loss area. (3) The main land use change form in the study area during the study period was the regional conversion of cultivated land to forest land and construction land, which led to the increase of water conservation service and the reduction of food production services in the corresponding patches. However, such conversion had not affected the overall improvement of the three ecosystem services in the study area. (4) Ecosystem service hotspots have gradually changed from single service dominant to co-leading of two services. The area of food production-recreation hotspots continued to increase, indicating the synergy between them. The area of water conservation-recreation hotspots continued to decrease, indicating the trade-offs between them. Different types of ecosystem services improve in synergies in the Beijing-Tianjin-Hebei urban agglomeration in the process of urbanization by the improvement of agricultural technology and productivity and promotion of leisure and sightseeing agriculture, which provides experience for other cities.